Combining Ability Analysis of Hybrid Rice (Oryza sativa L.) Parental Lines for Yield, Grain Quality and Grain Zinc Content (Bangladesh Rice Journal, 2025)
Combining ability analysis assists in identifying parents with high general combining ability (GCA) effects and cross combinations with high-specific combining effect (SCA) to exploit heterosis and isolate pure lines from the progenies of heterotic hybrids. An experiment was conducted at the experimental field of the Genetics and Plant Breeding department, Bangabandhu Sheikh Mujibur Rahman Agricultural University during Aman season 2017-2018 using 25 hybrids obtained from 5 x 5, line x tester mating design. Analysis of variance of combining ability showed highly significant differences among the genotypes indicating wider genetic variability among genotypes. Significant General Combining Ability (GCA) and Specific Combining Ability (SCA) effects were obtained for all the characters studied except 50% flowering, panicle length, and grain breadth. Among the lines GAN46A, IR58A and IR62A showed significant GCA effects for grain yield, and most of the yield contributing traits could be used as good general combiner lines for improving the grain yield of rice. IR68A line is good general combiner for Zn and Fe content. Among testers, Hera5R, ACI1R and KataribhoghR testers are good general combiner for Zn and Fe content. Hera5R and ACI1R testers having positive GCA effect with yield (t/ha). IR58A x BU7R, IR58A x BHD1R, IR62A x Hera5R, BRRI1A x Hera5R, BRRI1A x BHD1R, BRRI1A x ACI1R, GAN46A x BU7R, GAN46A x BHD1R, GAN46A x ACI1R crosses are good specific combiner for zinc content with grain yield (t/ha).Bangladesh Rice J. 27(1): 61-73